2021
DOI: 10.1111/jgh.15688
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound‐guided gallbladder and bile duct drainage with lumen apposing metal stent: A large multicenter cohort (with videos)

Abstract: Background and AimCholecystectomy and endoscopic retrograde cholangiopancreatography are the gold standard for managing acute cholecystitis and malignant biliary obstruction, respectively. Recent advances in therapeutic endoscopic ultrasound (EUS) have provided alternatives for managing patients in whom these approaches fail, namely, EUS‐guided gallbladder drainage (EUS‐GB) and EUS‐guided bile duct drainage (EUS‐BD). We aimed to assess the technical and clinical success of these techniques in the largest multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The type of misdeployment was not properly described in 31 (45.6%) EUS-CDS. Seven other causes of technical failure were reported in four studies[ 15 , 22 , 24 , 38 ]: 1 massive bleeding, 1 inability to puncture the bile duct, 2 duodenal perforations, 1 failure of fistula creation, 1 mechanical failure and 1 patient intolerance. In three studies[ 31 , 33 , 37 ], the effective rescue therapy after LAMS misdeployment was considered a technical success by the authors and in one study[ 15 ] duodenal perforation during dilation of the fistulous tract was the cause of technical failure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The type of misdeployment was not properly described in 31 (45.6%) EUS-CDS. Seven other causes of technical failure were reported in four studies[ 15 , 22 , 24 , 38 ]: 1 massive bleeding, 1 inability to puncture the bile duct, 2 duodenal perforations, 1 failure of fistula creation, 1 mechanical failure and 1 patient intolerance. In three studies[ 31 , 33 , 37 ], the effective rescue therapy after LAMS misdeployment was considered a technical success by the authors and in one study[ 15 ] duodenal perforation during dilation of the fistulous tract was the cause of technical failure.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 213 studies using our search strategy; 185 studies were excluded since they did not meet inclusion criteria. A total of 28 studies reported cases of EUS-GBD[ 8 , 22 , 29 , 37 , 40 - 63 ] including 16 studies in which LAMS misdeployment occurred[ 22 , 29 , 50 - 63 ]. The study flow chart is shown in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure was performed by a single pancreato-biliary endoscopist (Saurabh Gupta) at both sites who is a highly experienced endosonographer and has previously published 16 Research Ethics and Governance approval of the audit was granted by Adventist HealthCare Limited. Data from electronic medical records was used to determine baseline demographics, etiology and location of the obstruction, and diet tolerability according to the GOO scoring system (0 representing no oral intake, 1 for liquid diet only, 2…”
Section: Methodsmentioning
confidence: 99%
“…The procedure was performed by a single pancreato‐biliary endoscopist (Saurabh Gupta) at both sites who is a highly experienced endosonographer and has previously published 16 on the use of LAMS in the gallbladder and biliary tract. He is an active member of the EUS special interest group within the Gastroenterology Society of Australia and runs EUS training workshops within Asia Pacific.…”
Section: Methodsmentioning
confidence: 99%